40AR/39AR GEOCHRONOLOGY OF THE ULTRAHIGH-PRESSURE METAMORPHIC QUARTZ-MAGNESITITE IN ZAHEBA, EASTERN JUNGGAR, XINJIANG - Niu H.C.; Shan Q.; Zhang H.X.; Yu X.Y. (My University, 2007)
High-ultrahigh pressure lherzolite, garnet-pyroxenite, quartz-magnesitite and retrograde eclogite occur in the Zaheba-Almantai ophiolites. The Si content ( pfu ) of phengite in quartz-magnesitites is more than 3.35 with the maximum up to 3.77, indicating they are the products of high-ultrahigh pressure metamorphism. K2O contents of quartz-magnesitite and its wall rocks i. e. serpentinized lherzolite are extremely low, and the ratio of Na/(Na + K) of phengite is less than 0.04. These geochemical characteristics show that the phengite should not contain any excess Ar and hence be an ideal mineral for 40Ar/39Ar dating. The precise 40Ar/39Ar dating of the phengite in quartz-magnesitite is 281.6 ± 2.5Ma. The characteristics of mineral chemistry display the phengite ad undergone retrograde metamorphism which represents the exhumation age of metamorphism. This study shows that the exhumation of the Zaheba-Almantai ophiolites took place in early Permian.
Keywords: 40AR/3*9AR DATING; PHENGITE; QUARTZ-MAGNESITITE; ULTRAHIGH PRESSURE METAMORPHISM; ZAHEBA-ALMANTAI OPHIOLITES; Permian; Paleozoic::Permian; Палеозой::Пермская